Do Programs for Runaway and Homeless Youth Work? A Qualitative Exploration From the Perspectives of Youth Clients in Diverse Settings - Gwadz, Marya; Freeman, Robert M.; Kutnick, Alexandra H.; Silverman, Elizabeth; Ritchie, Amanda S.; Cleland, Charles M.; Leonard, Noelle R.; Srinagesh, Aradhana; Powlovich, Jamie; Bolas, James (Frontiers in Public Health, 2018)
Runaway and homeless youth (RHY) comprise a large population of young people who reside outside the control and protection of parents and guardians and who experience numerous traumas and risk factors, but few buffering resources. Specialized settings have developed to serve RHY, but little is known about their effects. The present cross-sectional qualitative descriptive study, grounded in the positive youth development approach and the Youth Program Quality Assessment model, addressed this gap in the literature. From a larger sample of 29 RHY-specific settings across New York State, RHY ages 16-21 from 11 settings were purposively sampled for semi-structured in-depth interviews on their transitions into homelessness, experiences with settings, and unmet needs (N=37 RHY). Data were analyzed with a theory-driven and inductive systematic content analysis approach. Half of participants (54%) were female; almost half (49%) identified as non-heterosexual; and 42% were African American/Black, 31% were Latino/Hispanic, and 28% were White/other. Results indicated that because RHY are a uniquely challenged population, distrustful of service settings and professional adults and skilled at surviving independently, the population-tailored approaches found in RHY-specific settings are vital to settings’ abilities to effectively engage and serve RHY. We found four major themes regarding the positive effects of settings: 1) engaging with an RHY setting was emotionally challenging and frightening, and thus the experiences of safety and services tailored to RHY needs were critical; 2) instrumental support from staff was vital and most effective when received in a context of emotional support; 3) RHY were skilled at survival on the streets, but benefitted from socialization into more traditional systems to foster future independent living; and 4) follow-through and aftercare were needed as RHY transitioned out of services. With respect to gaps in settings, RHY highlighted: 1) a desire for better management of tension between youths’ needs for structure and wishes for autonomy; and 2) lack of RHY input into program governance. The present study advances our understanding of RHY, their service needs, and the ways settings meet these needs, as well as remaining gaps. It underscores the vital, life-changing, and even life-saving role these settings play for RHY.